Foreign Direct Investment and Economic Growth: A Comparative Study among East Asian Countries - Kotrajaras, Polpat (Asian Journal of Applied Economics, 2013)
Abstract In the past two decades, there was a major shift in the degree of foreign direct investment (FDI) in East Asian countries. FDI as a tool for technology transfer can contribute to economic growth but this would depend on the economic environment of the host economy. This studyexamines the effect of FDI on the economic growth of 15 East Asian countries. For the analytical purpose, the countries are classified by their economic conditions, i.e. levels of human capital, investment on infrastructure, and trade openness. The panel cointegration analysis with endogenous growth model is used to observe the effect. The analysis is based on time series data from 1990-2009. The results show that FDI does not necessarily enhance economic growth. FDI had a positive effect on the economic growth only in the countries that have the appropriate economic conditions. East Asian countries including Thailand need to invest more on fundamental infrastructure and human capital, and increase their degree of trade openness in order to gain more from FDI. Keywords : foreign direct investment, economic growth, East Asia countries, endogenous growth model JEL Classification : C33, F21, F43